2020
DOI: 10.1016/j.ijengsci.2020.103364
|View full text |Cite
|
Sign up to set email alerts
|

On thermomechanics of multilayered beams

Abstract: In this paper, the mechanical behavior of multilayered small-scale beams in nonisothermal environment is investigated. Scale phenomena are modeled by means of the mathematically well-posed and experimentally consistent stress-driven integral formulation of elasticity. The present research extends the treatment in [1] confined to elastically homogeneous nano-scopic structures. It is shown that the non-locality leads to a complex coupling between axial and transverse elastic displacements. Such a size-dependent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Simple mechanical models and quite complex [50,51] nonlocal formulations can be found in the literature nowadays, making various claims concerning the nonlocality of nanoscopic structures, carbon nanotubes in particular. Static [52] and dynamic [53] problems in homogeneous and composite structures [54][55][56] are addressed for both isothermal and nonisothermal environments. The nonlocal mechanics in the above works is based on the stress and strain fields in the neighborhood of a point under consideration and is also related to the size-effects in nanoscopic structures.…”
Section: Remark 2 a Separate Line Of Research Based On Size Effects H...mentioning
confidence: 99%
“…Simple mechanical models and quite complex [50,51] nonlocal formulations can be found in the literature nowadays, making various claims concerning the nonlocality of nanoscopic structures, carbon nanotubes in particular. Static [52] and dynamic [53] problems in homogeneous and composite structures [54][55][56] are addressed for both isothermal and nonisothermal environments. The nonlocal mechanics in the above works is based on the stress and strain fields in the neighborhood of a point under consideration and is also related to the size-effects in nanoscopic structures.…”
Section: Remark 2 a Separate Line Of Research Based On Size Effects H...mentioning
confidence: 99%
“…where M T ¼ 12=h 3 R h=2 Àh=2 θðx,z,tÞzdz is the thermal moment, and I ¼ bh 3 =12 is the inertia moment of the cross section. When equation ( 18) is substituted in (16), we obtain…”
Section: Problem Formulationmentioning
confidence: 99%
“…Many researchers have considered the mechanism of heat transfer and microbeam vibration. [13][14][15][16][17][18][19][20][21][22] The inclusion of different field effects, such as temperature or initial stress field effects, also represents an important problem in the simulation of microstructures and microscale systems. Initial stress is generated in the medium due to various factors, resulting from a tightening phase, temperature difference, shot pinning, varieties of gravity, differential forces external, etc.…”
Section: Introductionmentioning
confidence: 99%
“…When the distance between two objects is comparable to or less than the thermal wavelength, the photon tunneling effect plays an essential role in the thermal radiative transfer, greatly enhancing the near-field radiative heat transfer (NFRHT) past the Planckian blackbody limit by several orders of magnitude [1][2][3][4][5][6]. Numerous theoretical studies on the NFRHT between various materials and nanostructures have been performed, such as transfer between two planar surfaces [1,7,8], two nanoparticles [8,9], two gratings [10][11][12][13][14], one sphere and plane [15], three bodies [16], and so on [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Recently, many experimental reports have indicated that the NFRHT can exceed the blackbody limit for a plane-plane configuration [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%